Case Report: The aslanger pattern as an indicator of severe acute coronary syndrome - Chen, Ying Zhu; Yao, Zheng Yang; Lin, Li Wen; Luo, Qiao Yun; Li, Rong; Zhao, Xin Jun (Frontiers in Cardiovascular Medicine, 2025)
Current guidelines categorize acute coronary syndrome (ACS) into unstable angina, ST-segment elevation myocardial infarction (STEMI), and non-ST-segment elevation myocardial infarction (NSTEMI). However, this categorization paradigm can lead to the underrecognition of acute coronary occlusion (ACO), especially when electrocardiographic findings are atypical. The Aslanger pattern is a critical ECG signature characterized by isolated ST-segment elevation in lead III with concomitant ST depression in leads V4–V6. It is often associated with severe multivessel disease, poor prognosis, and high mortality. We present two cases of chest pain with ECGs consistent with the Aslanger pattern. Coronary angiography confirmed three-vessel disease, with ACO in at least one vessel and severe stenosis in another. Notably, Patient 1 suffered in-hospital mortality, while Patient 2 had an uneventful recovery, underscoring the impact of timely intervention. This report emphasizes the value of recognizing the Aslanger pattern to bridge a diagnostic gap in ACS, enabling early identification of ACO, prompt reperfusion therapy, and ultimately, improved patient outcomes.